Morphological Differences Align with Habitat Partitioning Among Three Species of Percina (Percidae: Actinopterygii) in the Roanoke River, Virginia - Michael M Calvert; Steven L Powers (Southeastern Fishes Council Proceedings, 2023)
The upper Roanoke River has three species of Percina (P. nevisense, Chainback Darter; P. roanoka, Roanoke Darter; and P. rex, Roanoke Logperch). Resource partitioning appears to be a key component of maintaining diverse fish assemblages with habitat and food partitioning cited as especially important in communities containing members of the same family. Some aspects of the diets of these species have been documented in the literature with only modest differences among them. Microhabitat data for adults of these species have also been published revealing differences in habitat occupied by each with P. roanoka living in the fastest, shallowest water and P. nevisense in the deepest, slowest water. In an effort to investigate morphological features that may be adaptations to these different microhabitats, 18 body measurements were taken from specimens of each species. Fineness ratios were calculated and compared among species. Natural-log transformed raw measurements were also included in a Principal Component Analysis (PCA). Measurements that loaded heavily in the PCA were tested for differences among species. Principal component (PC) two loaded heavily for body width, body depth, and dorsal fin height, while PC three loaded heavily for anal fin length and caudal fin depth. All of these measurements were different among at least two of the three species examined. The highest mean fineness ratio and thinnest body width was found in P. nevisense. The lowest fineness ratio and thickest body width was found in P. roanoka with P. rex having intermediate values. A taller spinous dorsal fin is found in P. nevisense, and a longer anal fin was found in P. roanoka. Percina rex had the largest caudal fin and smallest anal fin.
Keywords: Percidae; darters; fineness ratio; Percina roanoka; Percina nevisense; Percina rex